Effect of EXAPAR on some parameters of reproductive efficiency in buffaloes - KHANNA, SUDHIR; KHURANA, K L; TRIPATHI, V N; MANUJAH, ANUJ (The Indian Journal of Animal Reproduction, 2023)
Herbal uterine Cleanser and restorative Exapar (Dabur Ayurvet Ltd.) was evaluated ’in 1 O buffaloes which were about to calve. Exapar treated group showed° statistically significant improvement in (i) No. of services per conception and (ii) No. of buffaloes becoming- pregnant from all inseminations. Other parameters like (i) time taken for the expulsion of placenta, (ii) days taken to show first post partum heat and· (iii) average days-open were also studied.